Modernisasi Manajemen Pesantren Menyongsong Era Society 5.0 - AM Saifullah Aldeia; Nurul Qolbi Izazy; St Aflahah; Yuyun Libriyanti (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2023)
Modernization of pesantren management is an important agenda item to be implemented immediately in welcoming the era of "society 5.0." The massive use of technology and information in the era of "society 5.0" provides challenges as well as opportunities for pesantren to adapt substantively and administratively. The aim of this research is to get a description of the modernization of pesantren management carried out at the Pesantren Al-Kautsar Banjar in response to Society 5.0. This research used a descriptive-qualitative approach. The empirical research data collection techniques are carried out in two ways, namely, primary data collection through field research, interviews, and direct observation, as well as secondary data obtained from library sources. The results of the research show that the modernization of pesantren management has been carried out at the Pesantren Al-Kautsar Banjar with five indicators, namely intentionality, novelty, specificity, acceptability, and direction towards certain goals.